EFFECT OF CALCIUM STEARATE ON THE PRODUCTION OF ALUMINUM POWDER - Bositov M.; Abdulhayev A.; Toshmatov A.Y. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This work presents the conditions for passivation of the surface of a newly activated aluminum powder using calcium stearate, changes in its chemical properties during mechanical action. Experiments have shown that the rapid, self-sustaining reaction of activated aluminum with water occurs even at room temperature and leads to almost 100% hydrogen formation under appropriate operating conditions. The reaction rate can be controlled by the size of the aluminum particles, water temperature, metal activation conditions, and the metal-water mass ratio.